Market Sensing Today - Prince, Melvin; Priporas, Constantinos-Vasilios (Business Expert Press, 2015)
Today's practicing marketers and scholars are confronted with a wide array of conflicting and imprecise information about best practices by which to search, gather, consolidate and interpret market information. Consequently, the need has never been greater to optimize market sensing to generate managerial actions that efficiently and effectively utilize knowledge of emerging consumer needs and competitive threats. This book addresses these urgent concerns. In essence, Market Sensing Today will cover, in ground-breaking ways, the following marketing managerial areas: * marketing opportunities associated with conventional and progressive bases of segmentation. * trends in market segment size and growth affecting long-range planning. * strategic direction for reaching future goals. * managerial understanding of assumptions competitors make about themselves. * the direction of current market strategies. * adding to the knowledge of a firm's core competencies. * how new market knowledge is best integrated into a firm's market intelligence system. * best ways to ensure the quality of information underlying decisions. * how benchmarking improves with market sensing. * best approaches for translating business issues into projects. * ways that key information may be disseminated within firms. * how proposed strategic changes are promoted by market sensing. * roles customer satisfaction insights play in policy. This book will address these key issues and more, to advance theory, research and practice based on latest developments in this vital field. It will show how to re-formulate traditional models that no longer work.
Keywords: dept.mrk; faculty_collection